Diverse Functions of Secretory Phospholipases A2. (15th July 2014) - Shridas, Preetha; Webb, Nancy R.
Abstract : Phospholipase A2 enzymes (PLA2 s) catalyze the hydrolysis of glycerophospholipids at their sn-2 position releasing free fatty acids and lysophospholipids. Mammalian PLA2 s are classified into several categories of which important groups include secreted PLA2 s (sPLA2 s) and cytosolic PLA2 s (cPLA2 s) that are calcium-dependent for their catalytic activity and calcium-independent cytosolic PLA2 s (iPLA2 s). Platelet-activating factor acetylhydrolases (PAF-AHs), lysosomal PLA2 s, and adipose-specific PLA2 also belong to the class of PLA2 s. Generally, cPLA2 enzymes are believed to play a major role in the metabolism of arachidonic acid, the iPLA2 family to membrane homeostasis and energy metabolism, and the sPLA2 family to various biological processes. The focus of this review is on recent research developments in the sPLA2 field. sPLA2 s are secreted enzymes with low molecular weight (with the exception of GIII sPLA2 ), Ca 2+ -requiring enzymes with a His-Asp catalytic dyad. Ten enzymatically active sPLA2 s and one devoid of enzymatic activity have been identified in mammals. Some of these sPLA2 s are potent in arachidonic acid release from cellular phospholipids for the biosynthesis of eicosanoids, especially during inflammation. Individual sPLA2 enzymes exhibit unique tissue and cellular localizations and specific enzymatic properties, suggesting their distinct biological roles. Recent studies indicate that sPLA2 s are involved in diverse pathophysiological functions and for most part act nonredundantly.